Serum uric acid level as a prognostic biomarker in critically ill patients with sepsis-associated acute kidney injury: A retrospective single-center study - Zhenkui Hu; Chao Song; Jinhui Zhang (PLoS ONE, 2025)
Background The predictive value of serum uric acid (SUA) for clinical outcomes in patients with sepsis-associated acute kidney injury (SA-AKI) remained unclear. Therefore, this study aimed to evaluate the clinical significance of SUA in predicting all-cause mortality among critically ill patients diagnosed with SA-AKI. Methods This retrospective study examined 483 patients with SA-AKI at the Affiliated Hospital of Jiangsu University from January 2015 to July 2023. The primary outcome evaluated in this study was in hospital all-cause mortality. To assess the prognostic value of SUA, we employed receiver operating characteristic curves, restricted cubic splines, Cox regression models, and Kaplan-Meier survival analysis. Results The hospital mortality and intensive care unit (ICU) mortality reached 43.3% and 42.2%, respectively. Kaplan-Meier analysis showed that the risk of 30-day mortality (log-rank test, P < 0.001) and 60-day mortality (log-rank test, P = 0.001) was significantly higher in patients with hyperuricemia (HUA). Multivariate Cox proportional hazards analysis showed that elevated SUA levels were significantly related to all-cause mortality. After accounting for potential confounding factors, patients with HUA maintained a significant correlation with both hospital mortality [HR (95%CI): 1.462 (1.094-1.952); P = 0.010] and ICU mortality [HR (95%CI): 1.474 (1.096-1.983); P = 0.010]. Further examination using restricted cubic splines revealed a progressively increasing risk of all-cause mortality with rising SUA levels. Conclusions Higher levels of SUA were associated with an increased risk of both hospital mortality and ICU mortality in critically ill patients with SA-AKI. These findings suggested that SUA may serve as an independent prognostic marker for these patients.